Law Enforcement Against Online Prostitution Crimes Through the MiChat Application: Study of Decision Number 129/Pid.Sus/2021/PN KPH - Nixxon Rian P. Siahaan; Sriono Sriono; Wahyu Simon Tampubolon (International Journal of Science and Environment (IJSE), 2026)
Kepahiang District Court Decision Number 129/Pid.Sus/2021/PN Kph analyzed the application of electronic evidence in the investigation of online prostitution through the MiChat application by the Kepahiang Police. Defendants Sanelia Amelia and Monicxa Caroline were proven to have violated Article 45 paragraph (1) in conjunction with Article 27 paragraph (1) of Law No. 19 of 2016 concerning ITE in conjunction with Article 55 paragraph (1)¹ of the Criminal Code, with a prison sentence of 1 year and 3 months each. The main evidence includes the MiChat status ("open booking" of PSK), Messenger/WhatsApp chat, and digital forensics of the Oppo A12 cellphone which confirmed the communication history and distribution of information violating morality. This normative legal research shows the effectiveness of electronic evidence equivalent to Article 184 of the Criminal Procedure Code in conjunction with Articles 5 & 44 of the ITE Law, through chain of custody verification and forensic expert testimony. Challenges include the potential for data manipulation, overcome by the Digital Evidence First Responder method. This ruling strengthens the jurisprudence of cyber evidence in Indonesia, emphasizing the increased capacity of investigators for similar cases.The analysis focused on the role of electronic evidence such as status updates on the MiChat app containing codes offering sexual services, Messenger and WhatsApp conversation histories proving collaboration between the perpetrators, and digital photos used as "offered goods." This electronic evidence, obtained through digital forensic examination, served as the basis for the Panel of Judges' conclusion that the elements of "distributing, transmitting, and/or making accessible electronic information containing indecent content" were met.